2022
DOI: 10.1111/jonm.13741
|View full text |Cite
|
Sign up to set email alerts
|

Toxic leadership behaviour of nurse managers on perceived job satisfaction and productivity of nursing workforce in sub‐Saharan Ghana: A multi‐centre cross‐sectional study

Abstract: Aim This study aimed at assessing the nature and effect of toxic leadership of nurse managers on the perceived job satisfaction and productivity of the nursing workforce. Background Nursing job outcomes such as job satisfaction and productivity are influenced by various factors in the nursing practice environment including leadership. Due to rising health care expenses and depleting material resources, the productivity of nurses that is expected to improve the efficiency of health care organizations is mostly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 51 publications
2
22
0
1
Order By: Relevance
“…Nurse managers' leadership styles directly influence the attitudes of other team members and, therefore, nursing leaders' approaches are important for the efficiency and effectiveness Transformational leadership of nursing care (Labrague et al, 2020;Labrague, 2021;Ofei et al, 2022). Nursing leaders play important roles in empowering staff nurses, which is fundamental for the development of the nursing profession (Fischer, 2016;Moura et al, 2017;Ross et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nurse managers' leadership styles directly influence the attitudes of other team members and, therefore, nursing leaders' approaches are important for the efficiency and effectiveness Transformational leadership of nursing care (Labrague et al, 2020;Labrague, 2021;Ofei et al, 2022). Nursing leaders play important roles in empowering staff nurses, which is fundamental for the development of the nursing profession (Fischer, 2016;Moura et al, 2017;Ross et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in publications on transformational leadership in the field of nursing in the 2000s may be linked to the growing competition in the health sector because as health organizations realized the importance of keeping nurses satisfied and motivated at work to avoid turnover, that impairs nursing care and, consequently, the productivity of the health institution, nursing leadership has gained prominence and the transformational leadership style has become more addressed (Devi et al , 2020; Herman et al , 2015). However, several studies show that nurses remain dissatisfied with their leaders (Guo et al , 2022; Ofei et al , 2022). Another fact that may have favored the increase in the production of articles on transformational leadership from 2008 onward is that between 2008 and 2010 the ICN chose topics related to nursing leadership as themes for International Nurses Day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, it is reported that toxic leadership has not received the scientific attention it deserves and has a small percentage in leadership research (Gandolfi and Stone, 2022). It is seen that these studies are mostly conducted in Western countries and focus on the causes and prevalence of toxic leadership (Abdelaliem and Zeid, 2023;Guo et al, 2022;Ofei et al, 2022). In addition, a meta-analysis by Schyns and Schilling (2013) emphasizes the negative effects of destructive leadership and suggests that there is a need for studies that conceptualize toxic leadership.…”
Section: Toxic Leadershipmentioning
confidence: 99%